A função da escola: significações de alunos do Ensino Médio de São Paulo pós pandemia - Cansone, Juliana Luci (2024)
In 2007, Michael Young published an article titled “What are schools for?” highlighting the discussion about the functions and purposes of the scholar education. Several authors were committed to investigating this issue, emphasising Lenoir (2013) in France and Libâneo (2013) in Brazil. According to these two authors, purposes and functions are created based on pedagogical and ideological biases that stipulate the path that the school must follow and objectives that it must fulfill. Therefore, they impact curriculums, pedagogical projects, educational policies, the teaching-learning process and daily school life. So, when we study the social function of the school, society's interest in the school is exposed. It is important to highlight that this research is being carried out after the end of the COVID-19 pandemic, a historical period that was very impactful for the areas of health and the national economy, as well as for education. Due to social isolation, a way to reduce the spread of the disease, schools had their classroom lessons suspended and had to introduce remote lessons. With this, a scenario was created in Brazilian education and we saw an increase in school dropout rates. According to Unicef research (2021), 5 million young people were without access to education in 2020, with studants aged 4 to 5 and aged 15 to 17 the most affected groups. The main reason that of all age groups reported for not being studying in pandemic times was the lack of interest in studying. This information is not new, in 2015 Abramovay's research, the author reported that participants between 13 and 15 years old did not attend school due to the lack of interest in studying. Based on that, this research sought to understand how students signify the role of the school. To capture these meanings, the theoretical perspective of Socio-historical psychology and the analysis procedure of Meaning Nuclei were chosen (AGUIAR, OZELLA, 2016). The results found indicate that students consider the function of school to be preparation for entry into higher education, as a means of improving their lives, which they understand as social ascension. The meanings of these young people express the contradictions that exist at school. At the same time that they signify that school is purpose to improve their lives, they also think it is the obstacle that impede them from doing so. They belive that the school should teach content that prepares them for life in society, but they state that the content taught is not useful and does not relate to their social reality. They signify that school should prepare them for entry into higher education, but they see this stage of education as something distant and unattainable for them with the basis of education they receive. In other words, the function of the school itself is contradictory because it does not match the school reality and is distant from the life they have